Changes to the Editorial Board - Liu, Tsu-Jae King (IEEE electron device letters, 2016)
IT is my pleasure to welcome Prof. Tomás Palacios to the Editorial Board of IEEE Electron Device Letters. A biography and sketch of Prof. Palacios' research interests can be found below. His subject areas are Compound Semiconductor Devices, Emerging Technologies and Devices, and Solid-State Power and High Voltage Devices.